An investigation to the impact of organizational green practices and organizational culture on generation-Z employee retention in Bangladesh - Tabassum, Sabiha (BRAC University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.